Badarawuhi: Representation of The Monstrous Feminine in The Film KKN di Desa Penari (2022) - Mustika Andini (Universitas Pendidikan Indonesia, 2023)
The film KKN di Desa Penari (2022) succeeded in reviving the Indonesian horror film industry for its achievement as the 2nd best seller movies in Indonesia, after Avengers: End Game (2019). As the title suggests, the film KKN di Desa Penari (2022) tells the story of six students who get a lot of disturbance and terror from the supernatural village rulers when carrying out the Kuliah Kerja Nyata (KKN) program and cause death. As women are often constructed as horrible figures in the product of patriarchal culture, the film KKN di Desa Penari (2022) introduces a new female ghost figure in Indonesia known as Badarawuhi. As a film study, this research uses Gerard Genette's theory of narratology (1980) which focuses on the concepts of frequency and focalization. Barbara Creed's (1993) framework of thinking about monstrous feminine and Julia Kristeva (1982) about abjection are also used to analyze how the representation of monstrous feminine is shown in the film KKN di Desa Penari (2022). The results of this study indicate that the figure of Badarawuhi who is a human-snake represents the monstrous feminine in the film as a castrator. Badarawuhi, who is polite, sensual, and seductive, has castrated Bima's masculinity as a male victim to the point of taking his life. Badarawuhi with her body and sexuality is considered as an abject that can disrupt the order of patriarchal life, so it must be removed by constructing her as a monstrous feminine.